Revenue management : a path to increased profits - Huefner, Ronald J. (Managerial accounting collection., 2015)
This book describes the emerging field of revenue management and its applications across a broad spectrum of business activities. It recounts the history and development of revenue management and addresses the analytical tools needed to integrate revenue management into management, in general, and financial and accounting practice, in particular. The book discusses and assesses various pricing practices and other revenue management techniques. It gives particular attention to the role of capacity analysis and the connection of revenue management to the theory of constraints. Although revenue management originated in the service industry, it is now practiced across a broad spectrum of business and not-for-profit organizations. This book will be a useful guide to managers at all levels who wish to give greater consideration to the importance of revenue management in their organizations. The second edition reorganizes the presentation of the subject, adds many new examples, and concludes with a chapter on emerging issues.